INTERNAL MANAGEMENT PROCESSES IN THE CIVIL CONSTRUCTION COMPANY: a case study - Tomioka, Aparecida Massako; Armas, Osvaldo Fernando de; Neves, José Manoel Souza das; Piacente, Fabrício José (Revista Interface Tecnológica, 2020)
The Brazilian construction industry is one of the most important sectors for the country ́s economy. Its vast supply chain mobilizes diverse sectors of the productive environment and is an important pole generating employment and income. In the last four years the Brazilian civil construction industry has been through one of the most turbulent periods of its history caused by an internal scenario of social, political and economic conflicts. In this same context, changes in organizational structures are observed to ensure the strategic adaptation of the organization to this scenario of change. In order to identify the main factors that contribute to overcome the challenges in a company in the civil construction sector, this work was carried out through a single case study, with the application of a survey questionnaire, in one of the sectors of the company. The researched company went through a downsizing process, changing its organizational structure, reducing resources and adapting to new market demands. Although the strategies adopted by the organization aim to improve productivity, reduce costs, improve processes and systems, it is observed that alfa is still in a scenario of changes. Its functional characteristic makes it difficult to reach the premises of a downsizing by minimizing bureaucracy and allowing an improvement in productivity and processes.